Linguistics, Communication and Knowledge Transference in Society: A Challenge for the 21st Century (Palimpsesto, 2019)
The objective of this article is to describe the current tasks associated to expert knowledge transference to society. Experiences dealing with the movement that fight for the rights of citizens to understand the language of public administration are described. These experiences question the meaning of writing in the 21st c., particularly in the field of professional education in technology and law where the challenge is to acquire linguistic and communicative tools for public communication. We conclude that for transference consulting the issue is to design projects for the comprehension of texts and take responsibility for their results. From this perspective it is possible to formulate a linguistics of optimization.
Keywords: Knowledge transference; professional writing; professional education; communicative strategies; linguistics of optimization